Encontros e desencontros entre psicanálise e linguística: a presença de Jacques Lacan - Silva, Maria da Glória Vianna Amorim (2012)
In this study, we have broached the tension between two fields of knowledge in which language is the protagonist, Linguistics and Psychoanalysis. Our starting pointing was the text of Jean-Claude Milner (1995), to whom the explicit establishment of this relationship must be attributed exclusively to Lacan, who, building his work, has mobilized many of the theoretical achievements and concepts from Structural Linguistics. Thus, this dissertation privileges the moment where Psychoanalysis was founded, strongly influenced by two exponents of the Structuralism: Roman Jakobson, whose work was based on Ferdinand de Saussure‟s and Claude Lévi-Strauss‟s theories, who have founded, respectively, Structural Linguistics and Structural Anthropology. We aim to examine determined vicissitudes in Lacan‟s love for Linguistics that it is possible to infer from the works in which the psychoanalyst mobilized concepts from this science. In this manner, our aim was defining the singularity‟s outlines in Lacan‟s gesture that, keeping the separation between Linguistics and Psychoanalysis, intended, by gathering concepts from Linguistics, produce his most famous monologue: the well-known Lacanien Psychoanalysis. The main question of this dissertation was the following: How can we characterize the effects of the encounter between the psychoanalyst Lacan and Linguistics? In order to answer it, we have investigated some Jacques Lacan‟s Seminars and texts, published between 1945 and 1973, in which it is possible to apprehend the moment when Lacan takes Linguistics as a key to read Freud‟s texts. Three main aspects were taken into account: the linguistic sign (signifier and signified); the metaphorical and metonymical operations and the difference between statement and enunciation. Lacan has transformed them and has aggregated the notion of subject of desire from the unconscious. Even in the moment of most delight, Lacan has never employed Linguistics in the field of Psychoanalysis. When proceeding his theory‟s elaboration, he has abandoned Linguistics as a science, keeping interest in language. Linguistics and Psychoanalysis performs, thus, as very different language conceptions and from this results a relationship of incessant proximity and absolute heterogeneity (MILNER, 1995. p. 2)